2022
DOI: 10.3389/fenvs.2022.931893
|View full text |Cite
|
Sign up to set email alerts
|

Microbial water quality and health risk assessment in karst springs from Apuseni Mountains, Romania

Abstract: In Apuseni Mountains (North-Western Romania), many of the inhabitants live in rural communities with limited or no access to the centralized and controlled water supply. This study assesses the microbiological quality of six karst spring waters from Bihor County used by rural communities as drinking water sources. Twenty-four water samples collected in January, April, June, and November 2021 were analyzed for E. coli, total coliforms, intestinal enterococci, Pseudomonas aeruginosa, and heterotrophic plate coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Indeed, the same pathogens that were originally in these fermentation sites are in permanent contact with the product ready for consumption. In fact, this microbial contamination observed in river waters and spring water is justified by the fact that they are sources of open water supply regularly exposed to all kinds of anthropological activities that promote the increase and diversification of microbial contamination [11]. Studies conducted by Djuikom et al [12], Mbawala et al [13] and Alia [14] respectively in Douala, Ngaoundere and in Noun revealed fecal contamination by the individual or associated presence of Coliforms, Fecal Enterococci in rivers and springs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the same pathogens that were originally in these fermentation sites are in permanent contact with the product ready for consumption. In fact, this microbial contamination observed in river waters and spring water is justified by the fact that they are sources of open water supply regularly exposed to all kinds of anthropological activities that promote the increase and diversification of microbial contamination [11]. Studies conducted by Djuikom et al [12], Mbawala et al [13] and Alia [14] respectively in Douala, Ngaoundere and in Noun revealed fecal contamination by the individual or associated presence of Coliforms, Fecal Enterococci in rivers and springs.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial indicators may be quantified to determine the amount of organic contamination in groundwater (Szekeres et al, 2018;Hubbard et al, 2020;Khadra et al, 2022;Stupar et al, 2022;Li et al, 2023). The results of bacteriological parameters in the samples obtained throughout five sampling campaigns are moderate.…”
Section: Assessment Of Water Quality 421 Adequacy Of Water For Human ...mentioning
confidence: 99%
“…Microorganisms from human or animal excreta are the principal cause of microbiological contamination, which enters humans via contaminated groundwater from wastewater, landfills, or wastewater treatment plants, creating serious health problems (Lugo Luis et al, 2021). The presence of pathogenic bacteria in the water supply can lead to water-borne illnesses, such as salmonellosis, typhoid, paratyphoid, cholera, amoebic dysentery, poliomyelitis, and infectious hepatitis (Stupar et al, 2022). Coliforms and Escherichia coli are important bacterial indicators used to define water quality and health risks.…”
Section: Introductionmentioning
confidence: 99%